Physiotherapists’ knowledge about the diagnosis, treatment and physical activity of patients with idiopathic scoliosis - Wójcik, Piotr; Wójcik, Anna; Ewertowska, Paulina; Czaprowski, Dariusz (Frontiers in Medicine, 2024)
Idiopathic scoliosis (IS) is a three-dimensional spinal deformity with an unknown etiology which, when left untreated, can have negative health consequences. Physiotherapy plays an important role in the treatment of IS, which is why physiotherapists should have adequate theoretical and practical knowledge about IS diagnosis and treatment methods. The aim of this study was to assess physiotherapists’ knowledge about IS, its diagnosis, treatment and recommended physical activities for subjects with IS. The influence of post-graduate courses, workplace, academic degree, work experience, education and membership in associations dealing with spinal deformities was also analyzed. The study involved 116 licensed physiotherapists. The research method was a diagnostic survey, and the research tool was a self-designed questionnaire. The questionnaire which included demographic questions to elicit information about the respondents and questions concerning IS, its diagnosis, treatment and recommended physical activity in the course of IS. The questions were created according to the recommendation of the Society on Scoliosis Orthopaedic and Rehabilitation Treatment. In the questionnaire, the respondents’ knowledge was assessed on the percent scale (100–90% of correct answers – full knowledge, 89–60% of correct answers – good knowledge, 59–50% of correct answers – moderate knowledge, <50% of correct answers – poor knowledge). The physiotherapists correctly answered from 60 to 89% of the questions which meant their good level of knowledge of IS. Factors such as post-graduate courses, workplace and academic degree influenced the knowledge of Polish physiotherapists regarding IS (p = 0.003, p = 0.036, p = 0.05, respectively). Physiotherapists who completed courses based on physiotherapy recommended by SOSORT demonstrated a higher level of knowledge compared to those without postgraduate courses (p = 0.018). The physiotherapists who ran the private individual physiotherapy practice demonstrated a higher level of knowledge compared to those working in a hospital (p = 0.058). Work experience and education have no influence on the physiotherapists’ knowledge about IS. Polish physiotherapists have a good knowledge of IS. Post-graduate courses (courses on Physiotherapeutic Scoliosis Specific Exercises), the respondents’ place of employment (private individual physiotherapy practice) and academic degree influence the knowledge about IS. Work experience, education and membership in associations dealing with spinal deformities have no influence on the physiotherapists’ knowledge about IS.